Glucose syrups : technology and applications - Hull, Peter , 1934- (Wiley-Blackwell, 2010)
Intends to bring together the relevant information on the manufacture and use of glucose syrups. This book is suitable for those involved in the processing and buying of these syrups, and for scientists involved in the manufacture of food products in which the syrups are ingredients.